2008
DOI: 10.1016/j.pocean.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Trophic modeling of the Northern Humboldt Current Ecosystem, Part II: Elucidating ecosystem dynamics from 1995 to 2004 with a focus on the impact of ENSO

Abstract: a b s t r a c tThe Northern Humboldt Current Ecosystem is one of the most productive in the world in terms of fish production. Its location near to the equator permits strong upwelling under relatively low winds, thus creating optimal conditions for the development of plankton communities. These communities ultimately support abundant populations of grazing fish such as the Peruvian anchoveta, Engraulis ringens. The ecosystem is also subject to strong inter-annual environmental variability associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Winds in this system move along the Peruvian coast toward the equator before turning westward into the Pacific Ocean and result in year-round, nutrient-rich upwelling (Bakun & Weeks 2008). This cold, nutrient-rich coastal upwelling yields high levels of primary and secondary productivity and makes the HCS one of the world's most productive marine ecosystems (Carr 2001, Taylor et al 2008.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…Winds in this system move along the Peruvian coast toward the equator before turning westward into the Pacific Ocean and result in year-round, nutrient-rich upwelling (Bakun & Weeks 2008). This cold, nutrient-rich coastal upwelling yields high levels of primary and secondary productivity and makes the HCS one of the world's most productive marine ecosystems (Carr 2001, Taylor et al 2008.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Winds in this system move along the Peruvian coast toward the equator before turning westward into the Pacific Ocean and result in year-round, nutrient-rich upwelling (Bakun & Weeks 2008). This cold, nutrient-rich coastal upwelling yields high levels of primary and secondary productivity and makes the HCS one of the world's most productive marine ecosystems (Carr 2001, Taylor et al 2008.Aside from supporting a considerable abundance of flora and fauna, the HCS also supports large fishing industries (Bertrand et al 2004, Jahncke et al 2004, Thiel et al 2007). Indeed, ~16 to 20% of global annual fish production is derived from the region (Heileman et al 2009).…”
mentioning
confidence: 99%
“…These high estimates are nevertheless conservative given that they were back-calculated using an ecotrophic efficiency of 0.95. Back calculations must be taken with caution and should ultimately be complemented with dynamic approaches using Ecosim, preferably with long time series of functional groups biomasses, in order to better constrain the estimates (Guenette et al, 2008;Taylor et al, 2008a). Nevertheless, the existence of such a high macrozooplankton biomass is supported by Antezana (2002a) who described Euphausia mucronata with SHCE biomass values up to 500 g wet weight per 1000 m 3 within the oxygen minimum layer (Antezana, 2002b).…”
Section: Biomass and Catch Changesmentioning
confidence: 99%
“…This paper also provides the basis for further explorations of ecosystem dynamics (Taylor et al, this 2008a), wherein non-steady state simulations of ecosystem change during and following the 1997-98 EN are performed and evaluated. In dynamic models, biomass changes are expressed in form of coupled differential equations derived from mass balance models equations.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we focus on the Humboldt upwelling system, which is one of the most productive systems in the world (Daneri et al 2000;Bakun et al 2010;Taylor et al 2008;Garreaud and Falvey 2009;Oerder et al 2015) and provides between 15 and 20% of the world's fish extraction (Sherman and Hempel 2008). Several studies have identified an intensification of the upwelling-favorable winds throughout the warm season in the Southern Hemisphere (Bakun et al 2010;Belmadani et al 2013;Sydeman et al 2014;Rykaczewski et al 2015).…”
Section: Introductionmentioning
confidence: 99%